Levistilide A Promotes Expansion of Human Umbilical Cord Blood Hematopoietic Stem Cells by Enhancing Antioxidant Activity - He, Mei; Xu, Hui; Liu, Guangju; Yang, Ming; Zhang, Wenshan; Li, Yafang; Zhang, Hexiao; Wang, Chaoqun; Zhang, Yiran; Liu, Xiaolei; Xu, Shiqi; Ding, Yahui; et al. (Frontiers in Pharmacology, 2022)
Several approaches to expand human hematopoietic stem cells (hHSCs) clinically along with retainable capability of multipotential differentiation have been reported, but only a few have advanced to evaluation in clinical trials, which limits the application of HSC-based therapy. Here we show a phthalide derivative, Levistilide A (LA), can serve as a promising molecule to expand functional human umbilical cord blood (UCB) HSCs ex vivo. An in-house screen identified LA out of nine natural products as an outstanding candidate for hHSCs expansion. Additionally, our data indicated that LA treatment not only increased the numbers of phenotype-defined HSCs, but also enhanced their colony formation ability. Xenotransplantation assays showed that LA treatment could maintain unaffected engraftment of hHSCs with multilineage differentiation capacity. Further experiments revealed that LA enhanced the antioxidant activity of hHSCs by reducing intracellular and mitochondrial reactive oxygen species (ROS) levels. The identification of LA provides a new strategy in solving the clinical issue of limited numbers of UCB HSCs.